2009
DOI: 10.4103/1477-3163.56290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the XRCC1 codon 399 polymorphism on the repair of vinyl chloride metabolite-induced DNA damage

Abstract: Background:Recent epidemiologic evidence suggests that the common polymorphism at amino acid residue 399 of the x-ray cross complementing-1 (XRCC1) protein, a key component of the base excision repair (BER) pathway for DNA damage, plays a significant role in the genetic variability of individuals in terms of the mutagenic damage they experience following exposure to the carcinogen vinyl chloride (VC). The aim of this study was to provide support for the biological plausibility of these epidemiologic observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There is a suggestion that the XRCC1 399 Gln polymorphic variant plays a role as a genetic modifier for raising the formation of DNA adducts and DNA damage in individuals exposed to aflatoxin B1, cigarette smoke, 1,3butadiene, vinyl chloride metabolites, or styrene [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion that the XRCC1 399 Gln polymorphic variant plays a role as a genetic modifier for raising the formation of DNA adducts and DNA damage in individuals exposed to aflatoxin B1, cigarette smoke, 1,3butadiene, vinyl chloride metabolites, or styrene [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, molecular modeling of the BRCT1 domains of the normal and polymorphic forms of XRCC1 demonstrates that the 399 substitution produces significant conformational changes in this domain, including the loss of secondary structural features such as α-helices that can be critical for mediating protein-protein interactions that would allow XRCC1 to coordinate BER. [ 63 ] Also, studies of lymphoblasts from individuals of different genotypes exposed in vitro to the reactive metabolites of VC showed that cells with the XRCC1 399 homozygous variant Gln-Gln genotype had an approximate fourfold decrease in efficiency of repair of εA DNA adducts compared to cells with the homozygous wild-type Arg-Arg genotype [ Table 2 ],[ 60 64 ] resulting in an approximate 1.8-fold increase in mutation frequency in the polymorphic cells as measured by the HPRT assay.…”
Section: The Molecular Epidemiology Of Vinyl Chloride Carcinogenesismentioning
confidence: 99%